Trading Identities: Alternative Interpretations of Viking Horse Remains in Scotland. A Pierowall Perspective - Siobhan Cooke (Papers from the Institute of Archaeology, 2016)
Approximately seven per cent of the pagan Viking graves known in Scotland contained horse remains. This article presents a brief summary of the traditional interpretations of horse remains in burials of this period and presents an alternative interpretation of these remains with particular reference to the Viking cemetery at Pierowall, Westray, Orkney Islands which is dated c. AD 850–950. It is argued that the act of horse deposition at Pierowall should be understood in the wider social context of the Scandinavian Peninsula and Scottish Islands during the initial period of west-ward expansion and social and political upheaval. It is in this context that the act of horse burial performed a specific communicative function which served to create and strengthen cultural allegiances with trading groups travelling from the Scandinavian Peninsula towards the western seaboard of Scotland, and into the Irish Sea.
Keywords: Viking Burial Horse Remains Scotland